2012
DOI: 10.4319/lo.2012.57.4.1049
|View full text |Cite
|
Sign up to set email alerts
|

Ciliates as the crucial food source of larval fish in a shallow eutrophic lake

Abstract: We assessed feeding of planktivorous fish larvae on ciliate protozooplankton in shallow eutrophic Lake Võ rtsjä rv, Estonia to determine whether ciliates are an important part of larval fish diet. We collected larvae of the most common fish species and examined their gut contents by gut segmentation and epifluorescence microscopy. Ciliates were present in the gut of all fish larvae. Gut segmentation analysis showed clear differences in food composition between gut quarters. The hard-bodied food items were quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Planktonic ciliates form an especially important food for larval fish in Lake Võrtsjärv (Zingel et al ., ), accounting for c . 60% of the total carbon consumed by fish larvae, and the food requirements of larvae during first feeding stages in May and June could not be met without consumption of ciliates (Zingel et al ., ). Given the exogenous feeding (at the stage of growth when larval fish ingest live food) and the rapid carbon turnover rate of fast‐growing larval tissues (Weidel et al ., ), the low δ 13 C signatures of the smallest larval fish (δ 13 C ranged from −38.4 to −36.4‰) may reflect some use of methane‐derived carbon.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Planktonic ciliates form an especially important food for larval fish in Lake Võrtsjärv (Zingel et al ., ), accounting for c . 60% of the total carbon consumed by fish larvae, and the food requirements of larvae during first feeding stages in May and June could not be met without consumption of ciliates (Zingel et al ., ). Given the exogenous feeding (at the stage of growth when larval fish ingest live food) and the rapid carbon turnover rate of fast‐growing larval tissues (Weidel et al ., ), the low δ 13 C signatures of the smallest larval fish (δ 13 C ranged from −38.4 to −36.4‰) may reflect some use of methane‐derived carbon.…”
Section: Discussionmentioning
confidence: 89%
“…The most depleted carbon isotope signatures were measured for fish larvae ingesting ciliates and rotifers. Planktonic ciliates form an especially important food for larval fish in Lake Võrtsjärv (Zingel et al ., ), accounting for c . 60% of the total carbon consumed by fish larvae, and the food requirements of larvae during first feeding stages in May and June could not be met without consumption of ciliates (Zingel et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…; Zavala‐Leal, Dumas, Pena, Contreras‐Olguin & Hernandez‐Ceballos ; Hagiwara, Wullur, Marcial, Hirai & Sakakura ). Smaller prey such as ciliates and flagellates are used less often, and usually in experimental scale, although studies have revealed that they contribute substantially to larval fish diets in nature (De Figueiredo, Nash & Montagnes ; Friedenberg, Bollens & Rollwagen‐Bollens ; Zingel, Paaver, Karus, Agasild & Noges ). Several rearing experiments also revealed that ciliates and flagellates could enhance the survivorship of fish larvae, especially those with a smaller mouth (Nagano, Iwatsuki, Kamiyama & Nakata ; Tew et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ciliate are adequate as food sources for first-feeding fish larvae because feeding success is related to non-armoured prey, whereas feeding failure occurs with armoured dinoflagellates because these organisms may pass unaltered through the larval gut (Scura and Jerde, 1977;Lasker, 1981). Ciliates have been found to sustain the survival and growth of first-feeding larvae at other eutrophic shallow lakes (Zingel, 2012), and at Catemaco, they similarly sustain the threadfin shad fishery.…”
Section: Environmental Background For Ciliatesmentioning
confidence: 99%
“…Plankton ciliates drive biomass from autotrophic and heterotrophic picoplankton to upper trophic levels; therefore, the abundance of autotrophic and heterotrophic picoplankton abundance was simultaneously recorded. Based on their size and other features, plankton ciliates are the most likely food source for first-feeding larvae of fish species that support local fisheries, and because this stage is considered critical in fish life cycles, the maintenance of fish stocks depends on ciliates (Zingel et al, 2012). The selective filter-feeding activity of these fish species is believed to be at least partially responsible for Catemaco's plankton composition (Kormákova and Tavera, 2003).…”
Section: Introductionmentioning
confidence: 99%